2007
DOI: 10.1080/14763140701324966
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic comparison of a side-foot soccer kick between experienced and inexperienced players

Abstract: The aim of this study was to identify critical kinetic variables that lead to increased ball velocity during a side-foot passing kick in soccer. Seven experienced male soccer players and eight inexperienced players participated in the experiment. They were instructed to perform side-foot kicks along the ground with maximum effort with an eye on the target line. The joint angles, angular velocities, and torques of the kicking leg were determined based on the three-dimensional kinematic data. The mean ball speed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
8

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 4 publications
2
22
0
8
Order By: Relevance
“…Além disso, o corpo pode assumir posturas diferentes de acordo com o alvo e velocidade da bola 4 . Estudos anteriormente realizados encontraram positivas correlações entre a velocidade do pé imediatamente antes do momento do impacto com a bola na velocidade da bola imediatamente após o contato [8][9][10] . Adicionalmente, o comportamento da velocidade da bola após um chute de força máxima do membro dominante e não dominante pode ser afetado principalmente pelas diferenças na velocidade do pé e na mecânica de colisão 11 .…”
Section: Introductionunclassified
“…Além disso, o corpo pode assumir posturas diferentes de acordo com o alvo e velocidade da bola 4 . Estudos anteriormente realizados encontraram positivas correlações entre a velocidade do pé imediatamente antes do momento do impacto com a bola na velocidade da bola imediatamente após o contato [8][9][10] . Adicionalmente, o comportamento da velocidade da bola após um chute de força máxima do membro dominante e não dominante pode ser afetado principalmente pelas diferenças na velocidade do pé e na mecânica de colisão 11 .…”
Section: Introductionunclassified
“…Joint moments on the instep kick in the present research were similar to values previously reported in literature in amateur, highly skilled and professional male soccer players (Kellis & Katis, 2007;Navandar et al, 2013), but higher than those reported for experienced male soccer players in the side-foot kick (Kawamoto et al, 2007) and in post-pubertal female soccer players (Lyle et al, 2011) The difference could be explained to the difference in maturity and skill level of the players (Katis et al, 2015) and the type of kick (Nunome et al, 2002).…”
Section: Figure 17: Sequential Increase Of Angular Velocities Seen Insupporting
confidence: 79%
“…The knee continues to flex and reaches a peak flexion (Kawamoto et al, 2007) ( Figure 5). This is known as the leg cocking phase (Kawamoto et al, 2007;Lees, 2013).…”
Section: Figure 4: Maximum Hip Extensionmentioning
confidence: 99%
See 2 more Smart Citations